KAJIAN HADITS TENTANG MODEL PROBLEM SOLVING DALAM PERSPEKTIF ISLAM - Nazaruddin Nazaruddin (Lembaga Sepercenter, 2025)
Problem solving is an important skill in everyday life, including in the context of education and decision making. In Islam, the concept of problem solving has been widely studied through the hadiths of the Prophet Muhammad which provide guidance in solving various problems. This article aims to examine the hadiths related to the problem solving model and analyze how the Prophet methods in dealing with various social, legal, and educational problems. This study uses a qualitative approach with a content analysis method of relevant hadiths. The results show that the Prophet applied several problem solving strategies, such as deliberation, empathy-based approach, and gradual problem solving. The findings provide insight into how the principles of problem solving in Islam can be applied in various aspects of life.